Reduced Sensitivity to Sooner Reward During Intertemporal Decision-Making Following Insula Damage in Humans - Sellitto, Manuela; Ciaramelli, Elisa; Mattioli, Flavia; di Pellegrino, Giuseppe (Frontiers in Behavioral Neuroscience, 2016)
During intertemporal choice, humans tend to prefer small-sooner rewards over larger-delayed rewards, reflecting temporal discounting (TD) of delayed outcomes. Functional neuroimaging evidence has implicated the insular cortex in time-sensitive decisions, yet it is not clear whether activity in this brain region is crucial for, or merely associated with, TD behaviour. Here, patients with damage to the insula (Insular patients), control patients with lesions outside the insula, and healthy individuals chose between smaller-sooner and larger-later monetary rewards. Insular patients were less sensitive to sooner rewards than were the control groups, exhibiting reduced TD. A Voxel-based Lesion-Symptom Mapping (VLSM) analysis confirmed a statistically significant association between insular damage and reduced TD. These results indicate that the insular cortex is crucial for intertemporal choice. We suggest that he insula may be necessary to anticipate the bodily/emotional effects of receiving rewards at different delays, influencing the computation of their incentive value. Devoid of such input, insular patients’ choices would be governed by a heuristic of quantity, allowing patients to wait for larger options.